(untitled) (International Journal of Engineering and Computer Science, 2014)
As the last few years have witnessed blistering excrescence in video coding technology, one of the prevailing fields of interest is to expound an establishment with authentication and copyright protection methodology embedded within an efficient video codec. In this paper, we put through a scrutiny on available and accessible video watermarking techniques. In later past, there has been a discernible quickening in information substitution over the web and the broad utilization of computerized media. The mounting interest with reference to digital watermarking throughout the last decade is undeniably due to the boost in the need of copyright protection which has facilitated an enormous ascent in the applications of video watermarking in copy control, broadcast monitoring, finger printing, video authentication, copyright protection etc. The main aspects of such techniques are information hiding, capacity, security and robustness. Robustness is an essential element when it comes to Video Watermarking Techniques as in its presence, is not possible to eliminate the watermark without rigorous degradation of the cover content. In this paper, we introduce and institute the sundries of Video Watermarking and attributes necessitated to design a robust watermarked video for valuable application and focus on various domains of video watermarking techniques.